2013
DOI: 10.1016/j.cmet.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Rapamycin Treatment Has Differential Effects on Metabolism in Mice

Abstract: Summary The evolutionarily conserved target of rapamycin (TOR) signaling controls growth, metabolism and aging. In the first robust demonstration of pharmacologically-induced life extension in a mammal, longevity was extended in mice treated with rapamycin, an inhibitor of mechanistic TOR (mTOR). However, detrimental metabolic effects of rapamycin treatment were also reported, presenting a paradox of improved survival despite metabolic impairment. How rapamycin extended lifespan in mice with such paradoxical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
177
10
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(208 citation statements)
references
References 22 publications
14
177
10
2
Order By: Relevance
“…Rapamycin (4 mg kg −1 body weight) was administered to WT and Nrf2KO mice via i.p. injection every other day for 6 weeks (Fang et al ., 2013), and several markers of cellular senescence were measured in fat and lung tissues. We found that in fat tissue from Nrf2KO mice at basal state showed higher levels of β‐gal staining and proinflammatory cytokines (measured by mRNA) than WT controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapamycin (4 mg kg −1 body weight) was administered to WT and Nrf2KO mice via i.p. injection every other day for 6 weeks (Fang et al ., 2013), and several markers of cellular senescence were measured in fat and lung tissues. We found that in fat tissue from Nrf2KO mice at basal state showed higher levels of β‐gal staining and proinflammatory cytokines (measured by mRNA) than WT controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…with rapamycin at a dose of 4 mg kg −1 body weight (dissolved in ethanol then diluted with vehicle containing 5% Tween‐80 and 5% PEG400) or same volume ethanol diluted with vehicle as controls. The dosing was given at every other day for 6 weeks (Fang et al ., 2013). The mice were euthanized at 48 h after last dose of rapamycin and a thorough necropsy was performed.…”
Section: Methodsmentioning
confidence: 99%
“…3). In addition, it has been demonstrated very recently that the duration of mTOR inhibition with rapamycin is of critical importance for regulating metabolic homeostasis (65). While short-term treatment with rapamycin exerts detrimental effects on glucose homeostasis in mice, prolonged treatment (i.e.…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 99%
“…Interestingly, only 1 week of PF-4708671 treatment was found to improve fasting glucose whereas rapamycin further increased fasting hyperglycaemia in obese mice. In addition to fasting glucose, rapamycin treatment was also found to increase fasting insulinaemia as previously reported in various rodent models [19,20,28,29]. To determine the impact of S6K1 inhibition on glucose homeostasis, we next performed a glucose tolerance test (GTT).…”
Section: S6k1 Inhibition Increases Glucose Uptake In L6 Myocytesmentioning
confidence: 99%